THE EFFECT OF VIRTUAL TEACHING ON ATTITUDES OF SECOND LANGUAGE ACQUISITION DURING COVID-19 CONDITIONS OF INDONESIAN STUDENTS - Susi P. Kandati; Devilito P. Tatipang (English Education Department, 2021)
The intention of this study is to find out the effect of virtual teaching on attitudes of second language acquisition during Covid-19 condition. Most school quickly closed to protect the students and teachers from the virus. The study findings indicate that Virtual Teaching (VT) marked a positive change in the attitudes of the students. This study was performed both qualitatively and quantitatively. In order to find out the effect of virtual teaching on second language acquisition attitudes, a questionnaire was distributed. It was conducted at the Senior High School level. The questionnaire was distributed among 77 third year students of random Senior High School with a google form sent through WhatsApp due to the outbreak of Covid-19 pandemic. It was designed on five linear scales, with strongly disagreed (1), disagreed (2), neutrality (3), agreed (4), and strongly agreed (5) options which use English and Bahasa Indonesia. Research results show that virtual teaching (VET) marks a positive change in students' attitudes.